PEDAGOGICAL PSYCHOLOGICAL CORRELATIONS OF POTENTIALS AND ABILITIES - Līduma, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The existing diverse opinions of pedagogues on innate potentials and abilities stimulated carrying out of the research. The research provides characteristics correlations of potentials and abilities in musical activity. The theoretical basis is found in the verities on the essence of innate potentials and abilities by such psychologists as Rubinshtein, Teplov, Bodalev, etc, music psychologists’ (Mjasishchev and Gotsdiner etc.) verities on manifestations of giftedness and musicality levels. For promotion of pedagogically psychological means, the verities by psychologist Students, pedagogues Dekens and Vikmane are researched. The objective and subjective conditions for activating of potentials and abilities have been researched, the promotion practice of abilities has been analyzed at preschool pedagogical process in x primary school in the school year of 2013/2014.